Mitigating effect of chitosan-coated zinc oxide nanoparticles on cryopreservation-induced DNA damage in human spermatozoa - Pooja Suresh Poojary; Ajjappla Basavaraj Shreya; Srinivas Mutalik; Divya Sachdev; Neetu K. Taneja; Shamprasad Varija Raghu; Renu Pasricha; Hanumappa Ananda; K. Pramoda; R. Vani Lakshmi; Satish Kumar Adiga; Guruprasad Kalthur (Journal of Taibah University for Science)
Zinc, an essential micronutrient, is an important mediator of sperm function. Supplementation of zinc oxide nanoparticle (ZnONPs) to semen cryopreservation medium has shown beneficial effects on sperm function, mainly due to its antioxidant and membrane stabilization properties. However, the ZnONPs are known to be membrane impermeable. In the current study, we explored the beneficial properties of membrane permeable zinc oxide nanoparticles on semen cryopreservation outcome. For the study, 52 liquefied human ejaculates were cryopreserved with chitosan-coated ZnONPs and stored in liquid nitrogen for one week. Samples were thawed and assessed for the sperm functional characters and DNA integrity. Significantly higher motility (P < 0.05), prolonged survival (P < 0.05) and lower DNA damage (P < 0.05) was observed in spermatozoa of semen samples cryopreserved with chitosan-coated ZnONPs. In conclusion, the presence of chitosan-coated ZnONPs in the ejaculate prior to cryopreservation increases the survival and decreases DNA damage without compromising with the functional competence of spermatozoa.